2022
DOI: 10.21009/jisae.v8i1.26011
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception and Practices on Giving Feedback on Students’ Work During Online Learning

Abstract: The aims of this study focused on looking at teachers’ perception and practice of giving feedback and also their challenges of giving feedback during online learning. This study used a descriptive qualitative method and online questionnaire was used to collect the data. The result of this study found that, teacher had a positive perception on the process of giving feedback. About 90% of teachers revealed that feedback was given to communicate about the gaps in performance, teachers’ expectation, affirming the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It is because the interaction between learners and their teachers is facilitated through online circumstances. The technical issues of online learning eliminated their opportunities to build synchronous communication (Harnin et al, 2022;Palvia et al, 2018). In line with this argument, it is also revealed that online learning causes learners to undergo contemplation, remoteness, stress, and lack of learning motivation (Arkorful & Abaidoo, 2015;Gillett-swan, 2017;Rahmayanti et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…It is because the interaction between learners and their teachers is facilitated through online circumstances. The technical issues of online learning eliminated their opportunities to build synchronous communication (Harnin et al, 2022;Palvia et al, 2018). In line with this argument, it is also revealed that online learning causes learners to undergo contemplation, remoteness, stress, and lack of learning motivation (Arkorful & Abaidoo, 2015;Gillett-swan, 2017;Rahmayanti et al, 2021).…”
Section: Introductionmentioning
confidence: 95%